2014
DOI: 10.1007/s12010-014-1275-6
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Production by Pure and Mixed Cultures of Chlorella pyrenoidosa and Rhodotorula mucilaginosa Isolated in Nuevo Leon, Mexico

Abstract: Given the well-known environmental drawbacks of using fossil fuels, advances in the field of alternative energy have become a worldwide technological priority. Special interest has been focused on the production of biodiesel obtained from oleaginous microorganisms. In the present research, lipid production by two species, microalgae Chlorella pyrenoidosa and yeast Rhodotorula mucilaginosa was assessed, independently and in mixed culture to evaluate a possible synergy. Fatty acid analysis was performed by gas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
1
4
0
2
Order By: Relevance
“…Besides that, Silva et al (2018) obtained, using the same strain as this present study, a total lipids percentage of 13.33% using a cassava wastewater dilution (50% v v -1 ) as substrate. Reyna-Martínez et al (2015) reported that their best lipid accumulation was about 20% from a Rhotodotorula mucilaginosa cultivation at a C/N of 12.5, what is close to the results reported in this paper.…”
Section: Oil-lipids Carotenoids and Fatty Acids Productionsupporting
confidence: 91%
“…Besides that, Silva et al (2018) obtained, using the same strain as this present study, a total lipids percentage of 13.33% using a cassava wastewater dilution (50% v v -1 ) as substrate. Reyna-Martínez et al (2015) reported that their best lipid accumulation was about 20% from a Rhotodotorula mucilaginosa cultivation at a C/N of 12.5, what is close to the results reported in this paper.…”
Section: Oil-lipids Carotenoids and Fatty Acids Productionsupporting
confidence: 91%
“…To our knowledge, this is the first report of Nuevo Leon, Mexico native microalgae, identified as C. sorokiniana and Scenedesmus sp., showing cytotoxicity against a murine lymphoma tumor cell line. Previous reports have shown microalgae potential for wastewater treatment and biodiesel production ( Reyna-Martínez et al, 2015 ; Beltrán-Rocha et al, 2017 ). In the present study, microalga isolates were grown under artificial light, closed photobioreactors, and previously established physicochemical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Biomass dried samples of C. sorokiniana and Scenedesmus sp. were placed in separate Whatman cellulose extraction thimbles (33 × 80 mm, thickness 1.5 mm) (Sigma-Aldrich, St. Louis, MO, USA) and placed in a Soxhlet extraction apparatus ( Reyna-Martínez et al, 2015 ), which is a continuous system consisting of a flat bottomed round flask, an extraction chamber with a siphon, and a condenser. This method was selected since this extraction is very practical and recommended by most of the methanol-soluble compounds for biological material recovering.…”
Section: Methodsmentioning
confidence: 99%
“…As biomassas produzidas no presente estudo são semelhantes às encontradas por Reyna-Martínez et al (2015), que produziram 6,27 g.L -1 quando cultivaram a levedura R. mucilaginosa em um meio sintético à base de glicose, extrato de levedura e peptona, e aos resultados de Cheng e Yang (2016), que obtiveram 6 g.L -1 de biomassa usando uma mistura de resíduos e melaço de cana, suplementados com extrato de levedura, como substrato.…”
Section: Consumo Do Substratounclassified
“…São úteis também para a produção renovável e sustentável de óleos biodegradáveis com potencial para uso em gêneros alimentícios, combustíveis e produtos químicos (SITEPU et al, 2014). Para a produção de lipídios, devem-se escolher linhagens que apresentem uma melhor cinética de desenvolvimento, com uma maior velocidade de crescimento, necessitando de menores tempos de cultivo, que não produzam substâncias indesejáveis e que tenham a capacidade de metabolizar substratos de custo reduzido (POLI et al, 2013).…”
unclassified